Enhancing disaster response of emergency medical teams through “TEAMS 3.0” training package—Does the multidisciplinary intervention make a difference? - Kaim, Arielle; Bodas, Moran; Camacho, Nieves Amat; Peleg, Kobi; Ragazzoni, Luca (Frontiers in Public Health, 2023)
Background: In the aftermath of disasters, Emergency Medical Teams (EMTs) are dispatched to help local rescue efforts. Although EMTs are recognized to be a critical component of the global health workforce, concerns have emerged over their functioning and effectiveness. For example, lack of cooperation and coordination between different EMTs has been a longstanding issue, resulting in fragmented disaster management. Methods: To enhance the provision of EMT’s field teamwork, the Training for Emergency Medical Teams and European Medical Corps (TEAMS) project was established, and later further updated with novel scenarios and exercises (ie, adapting EMT operations to a sudden disaster; becoming a modular team; reflecting on ethical dilemmas) in the complementary “TEAMS 3.0” project where a more comprehensive training package was developed. The aim of this study was to assess the effectiveness and quality of the TEAMS 3.0 training package in four training programs in Portugal, Germany, Norway, and Turkey. Participants completed a set of questionnaires designed to assess self-efficacy, teamwork, and quality of training. Results: The results from all the trainings suggest an improvement for both teams’ self-efficacy and teamwork. The mean score among all the participants (N=100) for both the the self-efficacy scale and teamwork scale was 3.217 (±0.223 SD) prior to training and 3.484 (±0..217 SD) following the training, and 2.512 (±1.313 SD) prior to training and 3.281 (±0.864 SD), respectfully, with statistically significant differences according to Wilcoxon paired samples test. The quality of training is regarded as high and deemed as an appropriate tool package for addressing the objectives of the project and the perceived needs of EMT disaster deployment. Conclusions: Thus far, the TEAMS 3.0 project has demonstrated to be effective in promoting EMT teamwork capacities.